The The witches of the Traditions - González Viaña, Eduardo (2019)
This is a data gathering in the Peruvian Traditions and in the Anales de la Inquisición de Lima about beliefs, magical rituals, power objects andconception of the world. There will be a comparison between these and those that belong to the present.